The Evaluation of the Agriculture of Hazelhazelnut in Duzce According to Climate Parameters - COŞKUN, Mücahit; SÖZEN, Erol (International Journal of Sustainable Agricultural Research, 2017)
Agriculture is a highly important economic activity in the world. Among the agricultural products of Turkey, hazelhazelnut is an important product for Turkey’s economy. More than 60 percent of the world hazelhazelnut production is made in Turkey. In this study, hazelhazelnut production in Düzce is examined in terms of possible climate effect in future. Because, Düzce is one of the important provinces in hazelhazelnut production. In th study, as a method, descriptive survey model has been used. In this method, existing situation on a subject is interpreted by searching. For this purpose, interpretation has been made by taking datum as to research from Ministry of Food, Agriculture and Livestock and Turkey Statistical Institute. These datum have been compared with weather data. In Düzce and in Turkey, hazelhazelnut production changing by years has been determined. It is seen that the largest factor to this is unexpected freeze and change of rainfall. It is reasoned that possible temperature increase in future and the effect of drought in Turkey and in Düzce that can effect agriculture of hazelhazelnut. Because, hazelhazelnut is selective and sensitive plant in terms of climate.